2020
DOI: 10.1186/s13058-020-01352-0
|View full text |Cite
|
Sign up to set email alerts
|

Circulating growth factor concentrations and breast cancer risk: a nested case-control study of IGF-1, IGFBP-3, and breast cancer in a family-based cohort

Abstract: Background Insulin-like growth factor 1 (IGF-1) and binding protein 3 (IGFBP-3) are associated with breast cancer in women at average risk of cancer. Less is known whether these biomarkers also predict risk in women with breast cancer family history. Methods We conducted a nested case-control study within the New York site of the Breast Cancer Family Registry (BCFR, n = 80 cases, 156 controls), a cohort enriched for breast cancer family history. Using conditional logistic regression, we estimated the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…Moreover, both NHS2 and CTS studies also demonstrate that this protective mechanistic interaction appears strongest against HR + breast cancer, producing a 30-40% reduction in this most common subtype of breast cancer. Furthermore, these concordant NHS2 and CTS ndings are consistent with numerous preclinical and clinical studies examining the role of the IGF-1 axis in driving HR + breast cancers [27][28][29][30]. At a mechanistic level, it is now well-established that tumorigenic crosstalk occurs between the estrogen receptor (ER) axis and epithelial signal transduction downstream of activated IGF1R, and that this crosstalk plays a role in both HR + breast cancer development and progression [52][53][54][55].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, both NHS2 and CTS studies also demonstrate that this protective mechanistic interaction appears strongest against HR + breast cancer, producing a 30-40% reduction in this most common subtype of breast cancer. Furthermore, these concordant NHS2 and CTS ndings are consistent with numerous preclinical and clinical studies examining the role of the IGF-1 axis in driving HR + breast cancers [27][28][29][30]. At a mechanistic level, it is now well-established that tumorigenic crosstalk occurs between the estrogen receptor (ER) axis and epithelial signal transduction downstream of activated IGF1R, and that this crosstalk plays a role in both HR + breast cancer development and progression [52][53][54][55].…”
Section: Discussionsupporting
confidence: 79%
“…IGF-1 plays an essential role in normal breast development; likewise, upregulation of the IGF-1 axis and increased IGF1R expression appears to be associated with the development of breast cancer [26][27][28][29]. A pooled analysis of 17 studies demonstrated that higher levels of circulating IGF-1 are associated with increased risk of breast cancer, with this being especially true for hormone receptor-positive (HR+) breast cancer [30]. Elevated serum levels or increased expression of IGF-1 has also been demonstrated in multiple non-breast cancers, and its role in cancer development is widely accepted [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…8 Similar associations also apply to women with a family history of breast cancer. 21 Total and calculated free oestradiol in pre-menopausal women Endogenous oestrogens may increase the risk of breast cancer by promoting cell proliferation and decreasing apoptosis. 1 Higher oestradiol concentrations have been consistently associated with an increased risk of post-menopausal breast cancer.…”
Section: Total and Calculated Free Testosteronementioning
confidence: 99%
“…This is particularly verified for the incurrence of estrogen receptor positive (ER+) tumors, independent from menopausal status ( Key et al, 2010 ). Whether it constitutes an additional risk for women with a family history of disease is not yet clarified ( Monson et al, 2020 ). However, an Italian study associated an increased risk of BC in patients with BRCA mutation (hereditary BC) with high serum IGF-1 levels ( Pasanisi et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%